Publication rates after the first retraction for biomedical researchers with multiple retracted publications. (4th July 2019) - Mistry, Vyoma; Grey, Andrew; Bolland, Mark J
ABSTRACT: Retraction of scientific publications can unmask scientific misconduct. We undertook a survey of publication rates, for authors with multiple retractions in the biomedical literature, to determine whether they changed after authors' first retractions. We collected publication and citation data from Scopus for 100 authors with multiple retractions (either >10 retractions or 2–5 retractions) in the Retraction Watch database. Publication rates increased until the year of the first retraction and decreased rapidly thereafter. By 4 years after the first retraction, the proportion of authors actively publishing at least one paper/year was <50%, annual publication rates were <50% of the pre-retraction rate, and only 22% of authors had a publication rate >50% of their pre-retraction rate. There was no difference in the decline in publication rates between authors associated with a retraction for misconduct and those not associated with such a retraction. After the first retraction, citation rates of retracted papers declined whereas those of unretracted papers by the same authors remained unchanged. In summary, publication rates of authors with multiple retractions, most of whom were associated with scientific misconduct, declined rapidly after their first retraction but a small minority continued to publish regularly.